Optimization of Instructional Technology for Attention Span in the Digital Generation - Rani, Shaumi; Pionera, Mutiarani; Kuswandi, Dedi; Wedi, Agus (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2025)
Exposure to technology causes a decrease in attention span in the digital generation which have an impact on the learning process. This provides an opportunity for learning technology to provide solutions to deal with this. This Systematic Literature Review aims to explore learning technology on attention span to optimize learning in the digital generation. The search strategy uses the PRISMA method with a qualitative descriptive approach collected from the Google Scholar, Scopus, and PubMed databases, resulting in 20 articles for analysis. The results of the study show that the phenomenon of attention span is closely related to cognitive load theory. Therefore, most of the approaches described prioritize dividing learning content into small parts and integrating it with various strategies so that the content attracts students' attention. Through active and collaborative learning models, student involvement will also increase, which will affect their attention span.